Breastfeeding without birthing: role of induced lactation - Jamani, Nurjasmine Aida (2020)
INTRODUCTION • There is exponential increase in number of visits for infertility in last decade. • It is estimated that 1 in 6 couples in the USA will experience difficulty in conceiving during the first year • 1-2% couples are involuntarily sterile. • Couples are less willingly to simply accept childlessness and aware of other options like adoption.